(3CYdGe GdfHhIs - (3CHh MGJe GdQGRj , eMeO Hf GOQjS Hf GdefPQ Hf OGhO Hf egQGf GdMfXj, CHh MGJe,J (B277 (3g` s ((3eMeO YHO GdbGOQ fLe GdOjf s)
(3ChdgG (B:s
(3ddg ef GdCLQ Ydi Pdc eSJYjfG Hg Yf LGQg aUd ajeG LQi Hjfi hHjf GdedMO Cfg fGXQfi ai CeQ GdfHhI , hChQO cdGekG fMh eG QSeg ai cJGHg GdPi bO PcQfGg s
(3BNQgG (B:s
(3aYdege ef cd TF jMJGL Edjg GdfGS ai CehQge OjfkG hOfjG, hdPdc ESJbGe CeQ GdYGde hde jTQc CMOkG ef Ndbg ai GdYde HgG ZdG GdfHi Ydjg GdSdGe , hgh YGde GdZjH MjK jLYd QSGdGJg hdG jTQc ai Mceg CMOkG Je GdcJGH Hef Gddg s
(3HgG fXGe GdJYbjHIs
(3HGdOGNd HjGVs
(3gPg GdfSNI GdJi UhQJ Yf OGQ GdcJH GdeUQjI JMJ Qbe (B2108 (3JGQjN bO UhQJ Yf GdLGeY GdcHjQ HUfYGAai GdeYgO fSNI CNQi HQbe (B1380 (3JGQjNs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs